Perkembangan Paradigma Ulama terhadap Kajian Fitrah dalam Maqāṣid al-Syarī‘ah - Muhammad Tahmid Nur; Syamsuddin Syamsuddin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This study describes the concept of fitrah and explains the development of ulama's paradigm of the concept of fitrah within the study of maqāṣid al-syarī’ah. This normative legal research presents the perspectives of the ulamas about this discourse. Content analysis was performed to identify the data based on several characteristics and different periods. The research concluded that fitrah meant the natural nature of creation in the form of inherent potential within human beings since their creation, distinguishing them from other creatures and guiding them towards embracing goodness and Shari'a. Furthermore, it was found that the paradigm regarding the position of fitrah in maqāṣid al-syarī’ah developed alongside the evolution of maqāṣid. The development can be classified into three periods. In the first period, fitrah filled the gaps between the nas in the legal development and it became a supporting argument. In the second period, fitrah was viewed in a broader perspective where it became the basis for the development of maqāṣid al-syarī'ah. In the last period, fitrah was understood as maqāṣid al-syarī'ah as the general purpose of the law or maqāṣid, which underlies almost all of the laws that the implementation is in accordance with sunnatullāh. The In-depth understanding of fitrah in maqāṣid al-syarī’ah directs to determine, choose and implement the law properly based on the human nature.